Effects of Inorganic Fertilizers on Virulence of the Entomopathogenic Nematode Steinernema glaseri and Peanut Germination under Field Conditions - Ibrahim E. Shehata; Mostafa M. A. Hammam; Mahfouz M. M. Abd-Elgawad (Agronomy, 2021)
The use of entomopathogenic nematodes as safe biopesticidal alternatives to hazardous chemicals entails improving the prediction of their native efficacy against soil pests. The effect of ten inorganic fertilizers, used extensively in Egypt, on the virulence of indigenous Steinernema glaseri and peanut germination was examined herein. The nematode added either before or tank-mixed with 1%, 5%, and 10% concentrations of each fertilizer in a peanut field was sampled 1 and 7 days before and 1, 7, 14, 21, 28, 49, and 56 post-tank mixes to check for S. glaseri virulence via baiting soil with Galleria mellonella larvae. Phosphorus fertilizers had more adverse effects than others on S. glaseri virulence and peanut germination. Plots with only S. glaseri had high germination close to chlorpyrifos. Averages of insect mortality in soil samples of potassium, nitrogen: phosphorus: potassium (NPK), nitrogenous, and phosphorus fertilizers, and non-fertilized checks (nematode only) were 85.8, 83.8, 80, 69.2%, and 93.3% respectively. Using S. glaseri is preferred before fertilizing. Most 1% fertilizer concentrations are compatible with S. glaseri in tank mixes for short-term (1–7 days) insect control but may affect long-term control.